2013
DOI: 10.1017/prp.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

New Constructs for the Prediction of Self-Initiated International Mobility: An Exploratory Study

Abstract: T his study aims to explore relationships between the motives for international mobility and observed mobility patterns. The key motives of 2,608 skilled expatriate New Zealanders were identified as cultural and travel opportunities, career, economics, affiliations, political environment, and quality-oflife. Mobility patterns, described here as the frequency, duration and cessation of mobility and the nature of the destination in terms of development level and cultural distance, were investigated. Desire for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Family and social connections have a great impact on the intention to stay or return (Richardson and McKenna 2006 ; Schoepp and Forstenlechner 2010 ) Weak host country pull and strong home country pull, along with shocks motivate repatriation (Tharenou and Caulfield 2010 ) After repatriation, adjustment to work is a stressful experience, since SIEs do not return to a role within an organization and have to reacquire local experience and rebuild networks (Begley et al 2008 ) Relationship with home and host country are fluid and subject to change due to adjustment and ease of communication (Beitin 2012 ) Desire for cultural and travel opportunities was the best predictor of cessation of mobility and development level in the host country. Career motives predicted duration of mobility and cultural difference of the destination (Thorn et al 2013 ) …”
Section: Comparing the Research Conducted Between 1997 And 2011 Versumentioning
confidence: 99%
See 3 more Smart Citations
“…Family and social connections have a great impact on the intention to stay or return (Richardson and McKenna 2006 ; Schoepp and Forstenlechner 2010 ) Weak host country pull and strong home country pull, along with shocks motivate repatriation (Tharenou and Caulfield 2010 ) After repatriation, adjustment to work is a stressful experience, since SIEs do not return to a role within an organization and have to reacquire local experience and rebuild networks (Begley et al 2008 ) Relationship with home and host country are fluid and subject to change due to adjustment and ease of communication (Beitin 2012 ) Desire for cultural and travel opportunities was the best predictor of cessation of mobility and development level in the host country. Career motives predicted duration of mobility and cultural difference of the destination (Thorn et al 2013 ) …”
Section: Comparing the Research Conducted Between 1997 And 2011 Versumentioning
confidence: 99%
“…This similarity in the motivational drivers among two different populations sparked some interest in identifying if there is a relationship between motives, mobility patterns and demographics. Thorn et al ( 2013 ) grouped the identified motives in six different categories: cultural and travel opportunities, career, economics, affiliations, political environment and quality of life. The influence of these motives on the mobility pattern showed that the desire for cultural and travel opportunities is the best predictor for mobility cessation and developmental level in the host country, while career motives predicted mobility duration.…”
Section: Comparing the Research Conducted Between 1997 And 2011 Versumentioning
confidence: 99%
See 2 more Smart Citations
“…Economic factors that pull people into a sector include employment or career development opportunities, opportunities for higher income or a better work environment. Non-economic factors include a better lifestyle and quality of life, and access to services and amenities, and social ones refer to those that are related to relationships, family and community concerns and group cohesion (Pinto, Cabral-Cardoso andWerther Jr, 2012, Thorn, Inkson andCarr, 2013) including strong connections with nature (York et al, 2016) and culture (Ho, Seet and Jones, 2016).…”
Section: Push-pull Theorymentioning
confidence: 99%